NILAI BUDAYA DALAM KONTEKS PENDIDIKAN KARAKTER PADA NOVEL SIRKUS POHON KARYA ANDREA HIRATA DAN IMPLIKASINYA DALAM PEMBELAJARAN TEKS NOVEL - Ridanta, Silvia; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTThe purpose of this study is to describe cultural values in the context of character education consisting of: (1) the value of discipline, (2) the value of hard work, (3) the value of responsibility, (4) creative value, (5)independent value, (6) the value of curiosity, (7) the value of appreciation, (8) the value of friendly/communicative, (9) the value of peace love, (10) the value of reading fondness, (11) the value pf caring for the environment, and (12)the value of caring for social character education in the novel Circus Pohon by Andrea Hirata. the research method is descriptive with the type of qualitative method. The background of this research is the novel Circus Pohon by Andrea Hirata. the research entry is an event unit in the novel Circus Pohon by Andrea Hirata. the presence of researchers in this study as observers. In this research there is no specific information. The main instrument of this research is the researcher himself. Data collection techniques in this study are observation techniques. This type of observation in this study is non-participant because the subject under study is a novel. Analyzing research data adjusted to the flow of analyzing qualitative research data. The research data are cultural values in the context of character education consisting of 12. The indicators of this study consist of 12. Kata kunci : Teks novel, novel Sirkus Pohon,  nilai pendidikan karakter